A docência e o ensinar na educação infantil: uma revisão de literatura a partir de teses e dissertações de 2015 a 2020 - Costa, Isabel Cristina Dornelas da (2022)
This work is the result of a research of an exploratory - explanatory bibliographic nature that has as its objective to investigate or that the literature indicates about teaching and teaching in Early Childhood Education. The research is linked to the Post-Graduation Program in Education of the Federal University of Lavras (UFLA), Research Line for Professional Teaching Development, Pedagogical Practices and Innovations, and the CNPq research group entitled: Research Group on Teacher Training and Pedagogical Practices (FORPEDI). The research allowed us to investigate the specificities of teaching and the possibilities of organizing teaching in Early Childhood Education, in the light of Historical-Cultural Theory, based on theses and dissertations produced in the period from 2015 to 2020. Historical-Cultural Theory, using contributions from contemporary Brazilian authors, being: Juliana Pasqualini (2010, 2015), Sonia Kramer (2005, 2009), Ana Beatriz Cerizara (2004), Mônica Appezzato Pinazza (2005, 2014) among others, who develop their studies on the specificities of teaching in this stage, such as Julia Oliveira-Formosinho (2002). To research we searched for jobs that we teach in Early Childhood Education, we found evidence of the teaching exercise directed to intentional and systematized pedagogical practice that promotes learning and development of children. A collection and selection of material from the Biblioteca Digital Brasileira de Teses e Dissertações (BDTD) resulted in another dissertações and five theses that revealed or analyzed non-daily concrete teaching practices of Early Childhood Education. Likewise, we systematize the analyzes in three categories: (1) principles of teaching: in which we evidence the research that analyzes teaching practices but discusses the role of teaching; (2) consequences of experience and subjectivities – jobs that provide evidence of the personal and professional trajectory that constitutes teaching and development in teaching practices and (3) knowledge and tasks in Early Childhood Education – jobs that show the knowledge and tasks that are Mobilized by teachers to teach children in the stage of Early Childhood Education. The research carried out allows us to affirm that it is possible to think about teaching practices in Early Childhood Education and in teaching committed to the specificities of parenting and that this should constitute an intentional route for the development of meaningful and contextualized pedagogical practices. As results, we show the knowledge and tasks that must be mobilized for the exercise of teaching in Early Childhood Education, highlighting that, for both cognitive knowledge, which advances initial and continuous training, the teachers who act in Early Childhood Education, articulate values, experiences, experiences, beliefs and principles that guide their actions with children. We conclude that teaching with small children should be focused on a theory that supports practice to overcome practice as simple dom. The Educational Product “Pedagogical Journey”, built from this research, broadens and exemplifies the pedagogical attitude of teaching in Early Childhood Education and encourages or recognizes different times and training spaces available on the Web.